The Role of Religious Leaders in Nurturing the Morals of Orphans in Budi Luhur Village - Batubara, Rinaldi; Khairuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
The role of religious leaders is very important in the moral development of orphans because they (orphans) have lost the figure of the head of the family, the backbone of the family, namely a father. In the formation of a child's morals, the father figure plays a very important role in it. Therefore, religious figures in the community can take this role universally towards orphans in their environment, in order to pay attention, protect and educate them. The purpose of this research is how exactly the role of religious leaders in fostering the morals of orphans, then what are the programs in fostering the morals of orphans and the obstacles faced in fostering the morals of orphans in Budi Luhur Village. The type of research conducted in this research is field research using a descriptive qualitative approach. The data collection techniques used are observation, interviews, and documentation studies. The data obtained was then analyzed using the Miles and Huberman technique. The research results of this study are: (1) The role of religious leaders in Budi Luhur Village is to convey amar ma'ruf nahi munkar; as a coach in shaping the morals of orphans; being a role model for the community; and mediator in times of conflict that hit the community. (2) The moral development program for orphans in Budi Luhur Village is compensation for the 27th night of Ramadan; compensation at residents' homes; and celebrations.